Anchoring and Risk Factors - Goukasian, Levon; Huang, Emily Jian; Ma, Qingzhong; Zhang, Wei (International Journal of Economics and Financial Issues, 2021)
Profitability and investment are becoming the new focus of empirical asset pricing. We examine the extent to which their return predictability is attributable to investors’ tendency to anchor on 52-week high. Based on a return decomposition methodology developed by George, Hwang, and Li (2014), two profitability measures (operating profitability, return on equity) and two investment measures (asset growth and investment to assets) are entirely attributable to anchoring. These results survive a battery of robustness checks and hold largely in various subsamples. The findings send a warning that these two potential risk factors could be attributed to the anchoring bias. Keywords: Profitability; Investment; Anomaly; Anchoring; Return decomposition JEL Classifications: G12, G14, G18 DOI: https://doi.org/10.32479/ijefi.11131